Reduction in the energy consumption from transport in Odense - Dorn-Jensen, Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 1994)
In most Danish cities we experience problems with the distribution of goods in the city centre. On the one hand the environment suffers from the impact of heavy lorries, and on the other hand the distributors have great difficulty in bringing goods to the city, because of traffic congestions and restrictions on the heavy traffic, enforced by the municipality. Since the traffic density in Danish cities is steadily growing, there will be increasing need for solutions of the problems. The municipality of Odense has initiated a project, in which the problems will be analysed in search for future solutions. In 1993 the Commission of the European Union granted support to the project within the framework of the SAVE Programme. The Danish Transport Council, which is established by the Danish government, is furthermore giving support to the project. Odense is the third largest town in Denmark with approximately 170.000 inhabitants.